Macrophage-derived exosomes accelerate wound healing through their anti-inflammation effects in a diabetic rat model. Issue 1 (4th December 2019) - Li, Mengdie; Wang, Tao; Tian, He; Wei, Guohua; Zhao, Liang; Shi, Yijie
Abstract: Chronic, subclinical inflammation was often observed in the diabetic wound area, causing inadequate and delayed wound-healing effects by failing to initiate cell migration, proliferation, and extracellular matrix deposition. Therefore, we presented macrophage-derived exosomes (Exos) and explored their potential for inhibiting inflammation and accelerating diabetic wound healing in a skin defect, diabetic rat model. A thorough investigation demonstrated that Exos exerted anti-inflammatory effects by inhibiting the secretion of pro-inflammatory enzymes and cytokines. Furthermore, they accelerated the wound-healing process by inducing endothelial cell proliferation and migration to improve angiogenesis and re-epithelialization in diabetic wounds.